HYPSOMETRY AND VOLUMETRY OF Eucalyptus urograndis IN A CROP-FOREST INTEGRATION SYSTEM - Cunha, Stephany Diolino; do Vale, Vagner Santiago; Ramos, Tatiana Vieira; Araújo, Matheus da Silva (Floresta, 2022)
Due to the positive impact that the eucalyptus species has on the Brazilian economy, it is currently the most used forest essence. The objective of this work was to evaluate different hypsometric and volumetric models for Eucalyptus urograndis clones (Eucalyptus urophylla S.T. Blak and Eucalyptus grandis W. Hill ex Maiden) in a Crop-Forest Integration (CFI) system. The trees were evaluated at 7 years of age and arranged in double rows, occupying 20.76% of the total system area. The individuals were subjected to rigorous volumetric cubing according to the Smalian method at intervals of one meter up to full height. The following models were evaluated for the collected height data: Linear, Trorey, Stofels, Curtis, Henriksen, Prodan, Chapman & Richards, Petterson and Bailey & Clutter. Furthermore, the Spurr, Hohenald-Krenn, Stoate, Schumacher Hall, Meyer, Husch, Ogaya and Takata models were used for volume data. The results were determined through the coefficient of determination (R2), standard error of the estimate in percentage (Syx%), significance of the regression coefficients (𝛽) and graphical distribution. The hypsometric model which best fit the database among tested models was the Prodan equation, with a coefficient of determination (R²) of 0.89, while the best result for volumetric models was found using the Meyer model, with a coefficient of determination (R²) of 0.99. All evaluated models were efficient in estimating the height and volume of the Crop-Forest Integration (CFI) system, thus demonstrating that GG100 eucalyptus is a good option in integrated systems.